Deteksi Produksi Toksin Stx-1 dan Stx-2 dari Escherichia coli O157:H7 Isolat Lokal Hasil Isolasi Feses dan Daging Sapi - I Wayan Suardana; I Gusti Made Krisna Erawan; Bambang Sumiarto; Denny Widaya Lukman (Jurnal Veteriner, 2009)
Shiga toxin produced by Escherichia coli O157:H7 can cause outbreaks and sporadic cases of serioushuman diseases. The diseases are indicated by hemorrhagic colitis and hemolytic uremic syndrome. Meatand meat products have been identified as vehicles of food borne disease caused by E.coli O157:H7. Themain aim of this research was to identify the correlation between the level of E.coli O157:H7 contaminationand the presence of Shiga toxin (Stx1 and Stx2) by applying method of Vero toxin Escherichia coli-ReversePassive Agglutination Test (VTEC-RPLA). The results showed that 3 of 7 isolates and 1 of 4 isolatesisolated from feces of cattle and beef, respectively produced Stx 1 (VT1). In the detection of Stx 2 (VT2), 4of 7 isolates and 1 of 4 isolates, isolated from the same samples were found to produce this toxin.According to all isolates, in this research showed, 1 isolate was found to produce VT2, 4 isolates to produceboth VT1 and VT2, while 6 isolates showed negative results either to VT1 or VT2.